What have we learned from the dead? A compilation of three years of cooperation between entomologists and crime scene investigators in Southern Brazil - Rodrigo C. Corrêa; Maria F.C. Caneparo; Karine P. Vairo; Alexandre G. de Lara; Mauricio O. Moura (Revista Brasileira de Entomologia, 2019)
ABSTRACT With homicide rates higher than the world average, Brazil stands out as one of the most violent countries worldwide. Time of death estimation based solely on body changes can be biased or inaccurate; forensic entomology can play a determinant role in such cases. Accurate knowledge of necrophilous fauna is essential to validate experimental data and allows for the application of entomological evidence in forensic investigations, which benefits scientists, investigators, and society in general. Entomological evidence from Curitiba and 22 nearby cities were collected by crime scene investigators from the Scientific Police of Paraná. The corpses were found in diverse environments and specimens from each species were collected from all life stages. We present data from 25 cases from 2011 to 2014, including associated species, new records, and comparisons between existing experimental data and data from species collected in the cases presented. We identified 23 total species, of which eight species of Coleoptera and two species of Diptera have not previously been recorded on corpses. In all cases, Calliphoridae (76%) and Silphidae (48%) were the most numerous families collected. Working together with the scientific police gave us insight into which species lacked detailed records and enabled us to collaboratively focus on resolving deficits in our knowledge of necrophagous insects.